Integrating Physical and Digital Assemblies. (June 2013) - Zarzycki, Andrzej
Computer-based tools have changed the focus and modes of design thinking in architecture. While often criticized for its overemphasis on formal expressions and its pursuit of the spectacular, digital creativity has begun to take into account a multiplicity of design factors that define architecture. These factors relate to performance simulation and analysis, constructability, and building information modeling (BIM). This paper discusses the use of physical and digital mock-ups in the context of building technology courses. It uses these mock-ups as an important vehicle that provides students with a feedback mechanism regarding often digitally idealized creative thinking.